Assessing Integration of Science in Policy-Making Process of the Utilization of Abandoned Lands in Indonesia: Case of Bogor Regency - Purwawangsa, Handian; Nurrochmat, Dodik Ridho; Kartodihardjo, Hariadi; Rustiadi, Ernan (Forest and Society, 2022)
Science cannot directly influence policy without a process of knowledge transfer and integration into policy-making called the science-policy interface. On the other hand, not all scientists intend to use their knowledge and findings to influence policy-makers. This condition causes a gap between science and policy. The main objective of this study is to identify various "knowledge products" that have varying amounts of policy space, understand the power relations between actors, and identify and analyze the process of integrating knowledge products into the policy-making process for abandoned land in Bogor Regency. The primary method used in this study is the RAPID (Research and Policy in Development) analytical framework. The study indicates that policy-makers will adopt the scientific evidence if they follow their organization's Main Performance Indicators (KPI) or gain political or economic benefits. The role of the lower-level bureaucracy as the implementing agency is crucial in the policy adoption process. The people "behind the organization" and "policy intrapreneurs" have an essential role in integrating scientific knowledge and policy. Scientific products, such as modeling, are often more effective in convincing policy-makers. The scientific evidence will become good advice and have a more significant impact when they meet policy-makers' interests. The study concludes that it is challenging to integrate science into policy-making without mutual trust amongst formal and informal network actors who have access to policy-makers to utilize abandoned lands in Bogor Regency.